Genetic sampling for estimating density of common species. Issue 16 (3rd July 2017) - Cheng, Ellen; Hodges, Karen E.; Sollmann, Rahel; Mills, L. Scott
Abstract: Understanding population dynamics requires reliable estimates of population density, yet this basic information is often surprisingly difficult to obtain. With rare or difficult‐to‐capture species, genetic surveys from noninvasive collection of hair or scat has proved cost‐efficient for estimating densities. Here, we explored whether noninvasive genetic sampling (NGS) also offers promise for sampling a relatively common species, the snowshoe hare ( Lepus americanus Erxleben, 1777), in comparison with traditional live trapping. We optimized a protocol for single‐session NGS sampling of hares. We compared spatial capture–recapture population estimates from live trapping to estimates derived from NGS, and assessed NGS costs. NGS provided population estimates similar to those derived from live trapping, but a higher density of sampling plots was required for NGS. The optimal NGS protocol for our study entailed deploying 160 sampling plots for 4 days and genotyping one pellet per plot. NGS laboratory costs ranged from approximately $670 to $3000 USD per field site. While live trapping does not incur laboratory costs, its field costs can be considerably higher than for NGS, especially when study sites are difficult to access. We conclude that NGS can work for common species, but that it will require field and laboratory pilot testing to develop cost‐effective sampling protocols. Abstract : Even for relatively common, easy‐to‐trap species, noninvasive genetic sampling (NGS) can be a viable alternative to traditional methods for estimating animal densities. In our study on snowshoe hares, NGS provided population estimates similar to those derived from live trapping, but a higher density of sampling plots was required for NGS. Increasing the density of NGS plots at a site is relatively easy and cheap, and an important field advantage of NGS is that surveys can be completed in a single site revisit, compared to the multiple nights required with live trapping.